PENGARUH PROFITABILITAS, PERTUMBUHAN, STRUKTUR AKTIVA DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL ( Pada Perusahaan Property Dan Real Estate Yang Terdaftar Di BEI) - B31111016, Deva Restira (Jurnal Manajemen Update, 2016)
The aims of this research were to found out and analyzed the influence of profitability, growth, structure of assets and the size of the company to the capital structure on a property and real-estate companies that listed on the Indonesia Stock Exchange. This research used secondary data that sourced from the financial statements of the Property and Real-estate company period 2010-2014 obtained from Indonesia Stock Exchange website. The selection of the sample in this research used purposive sampling method, with the 34 samples of Property and Real-estate company period 2010-2014 that obtained from Indonesia Stock Exchange website. This research used capital structure as the dependent variable and profitability, growth and structure of assets and the size of the company as independent variable. An analytical technique used was multiple linear regression analysis technique. The results showed that profitability and the size of the company doesn't significantly to capital structure while the growth and structure of assets have significant influence towards the capital structure. The magnitude of the determination coefficient adjusted R2 was 0.118. This means that 11.8 percent variable of capital structure can be explained by the independent variable in this research, while the rest 88.2 percent was explained by other variables out of this research model. Keywords: Capital Structure, Profitability, Growth, Structure Of Assets, The Size Of The Company.